2019
DOI: 10.1083/jcb.201804172
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinating enzyme USP30 maintains basal peroxisome abundance by regulating pexophagy

Abstract: The regulation of organelle abundance is critical for cell function and survival; however, the mechanisms responsible are not fully understood. In this study, we characterize a role of the deubiquitinating enzyme USP30 in peroxisome maintenance. Peroxisomes are highly dynamic, changing in abundance in response to metabolic stress. In our recent study identifying the role of USP30 in mitophagy, we observed USP30 to be localized to punctate structures resembling peroxisomes. We report here that USP30, best known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 27 publications
5
58
0
Order By: Relevance
“…USP30 is one of only two DUBs that possess a transmembrane domain. Its localisation is restricted to the outer mitochondrial membrane and to peroxisomes (18)(19)(20)(21). USP30 can limit the Parkin-dependent ubiquitylation of selected substrates and depolarisation-induced mitophagy in cell systems that have been engineered to over-express Parkin (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…USP30 is one of only two DUBs that possess a transmembrane domain. Its localisation is restricted to the outer mitochondrial membrane and to peroxisomes (18)(19)(20)(21). USP30 can limit the Parkin-dependent ubiquitylation of selected substrates and depolarisation-induced mitophagy in cell systems that have been engineered to over-express Parkin (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Opposing the action of PEX2 on peroxisomes is the deubiquitinating enzyme USP30 ( Figure 3B). First described as a mitophagy regulator [152], USP30 has been shown independently by two groups to regulate pexophagy by targeting to peroxisomes [103,104]. Marcassa, E., et al found that an endogenous portion of USP30 localizes to peroxisomes via an N-terminal transmembrane domain where it acts to reduce basal pexophagy [103].…”
Section: Peroxisome Designation For Degradation In Mammalsmentioning
confidence: 99%
“…Marcassa, E., et al found that an endogenous portion of USP30 localizes to peroxisomes via an N-terminal transmembrane domain where it acts to reduce basal pexophagy [103]. Riccio, V., et al subsequently reported that over-expression of USP30 prevents amino-acid starvation-induced pexophagy, by counteracting PEX2-mediated ubiquitination of PEX5 and PMP70 [104]. These studies highlight the importance of ubiquitin designation for pexophagy and demonstrate that dissipation of ubiquitin from peroxisomes serves to counteract pexophagy basally and during amino acid starvation.…”
Section: Peroxisome Designation For Degradation In Mammalsmentioning
confidence: 99%
“…4 Regulation of pexophagy is therefore essential to prevent disease, and thus formed the basis of our study. 5 Peroxisomes, like mitochondria, are degraded through selective autophagy, termed pexophagy and mitophagy respectively. Pexophagy can be induced by various stimuli, but the focus of our study was amino acid starvation induced pexophagy.…”
mentioning
confidence: 99%
“…Our published study aimed to characterize the role of USP30 in peroxisome maintenance. 5 We began by showing the targeting of USP30 to peroxisomes, demonstrating that over-expressed wild type USP30 is colocalized with peroxisomes significantly more than the mitochondrial targeted TOM20-USP30. Using a stop-anchor PEX16 (saPEX16) which is ER retained, we showed that USP30 can be recruited to the ER by the peroxisome membrane importer PEX16, while mitochondrial targeting remained intact, suggesting that USP30 is targeted to the peroxisomes with the assistance of PEX16.…”
mentioning
confidence: 99%